Study of Polymer Flooding Behavior in Heterogeneous Two-Layered Porous Media - Muhammad Taufiq Fathaddin; Kartika Fajarwati Hartono; Trijana Kartoatmodjo (Journal of Earth Energy Science, Engineering, and Technology, 2020)
In this paper, a numerical study was conducted to investigate the effect of spatial heterogeneity of multiple porosity fields on oil recovery, residual oil saturation,   polymer retained, and polymer adsorption. The generated porosity fields were applied to UTCHEM for simulating polymer and water flooding in heterogeneous two-layered porous media. From the analysis, the increase of reservoir heterogeneity resulted in higher polymer retention and lower polymer adsorption. In general, polymer flooding results in more balance residual oil saturation in the upper and lower layer than water flooding. This indicated that the vertical sweep efficiency of polymer flooding was better than water flooding. Residual oil saturation ratio between layers after water or polymer flooding was about equal along with the increase of reservoir heterogeneity. Spatial heterogeneity of multiple porosity fields had only a small effect on recovery factor. The variation of the recovery factor of polymer and water flooding due to the reservoir heterogeneity was under 1%.